Investigation of Mechanism for Intergranular Fatigue Crack Propagation of Low Carbon Steel JIS S10C in Hydrogen Gas Environment - NISHIKAWA, Hide-aki; ODA, Yasuji; NOGUCHI, Hiroshi (Journal of Solid Mechanics and Materials Engineering, 2011)
In order to investigate the mechanism for the intergranular fatigue crack propagation of a low carbon steel in a low pressure hydrogen gas environment, two kinds of examinations were carried out. One examined the effect of the cyclic pre-strain on the crack growth behavior. The other was the in-situ observation of intergranular fatigue crack propagation in a hydrogen gas environment. The main results are as follows. (1) SEM observation of the specimen surface morphology of a plain specimen fatigued in hydrogen gas showed that a gap at the grain boundary was induced by slip behavior, but not in nitrogen gas. (2) A specimen cyclic-prestrained in hydrogen gas showed slight influences on the increase in the crack propagation rate. (3) Mating intergranular facets on the fatigue fracture surfaces showed the matching of a striation-like pattern in the manner anticipated from the damage mechanism of (1). (4) The environment-change test from hydrogen to nitrogen during the fatigue test showed that intergranular facets appeared even in nitrogen. Results (3) and (4) suggests that the damaging process of (1) is valid in an actual fatigue crack. (5) In-situ observation of the crack propagation behavior in hydrogen gas showed that a crack propagated faster along the grain boundary. However, no visible discontinuous crack advances appeared as a large number of load repetitions was required. Phenomena considered to be a damage process (1) appeared ahead of a crack tip. Based on these results, a convincing mechanism for the intergranular fatigue crack propagation process is as follows. Grain boundaries just ahead of a crack tip are damaged due to the large number of hydrogen-enhanced slip repetitions, therefore, the fatigue crack becomes easier to propagate along the grain boundary in hydrogen.